The Pharisees: their Origin and their Philosophy - Finkelstein, Louis (Harvard theological review, 1929)
The brilliant light thrown upon the Pharisees and the Sadducees by the careful studies of Geiger and Wellhausen, and their many disciples, has not completely dispelled the obscurity whieh surrounds the origin and being of these ancient groups. Geiger, whose views have in the main been accepted by Graetz, Detenbourg, Weiss, and Klausner, conceived of the conflict between these sects as intrinsically similar to that which developed in his own day between the reform and orthodox Jews in Germany.